Obama's wars - Woodward, Bob, 1943- (New York : Simon & Schuster, 2010)
Woodward shows Obama making decisions on the Afghanistan War, the war in Pakistan and the worldwide fight against terrorism.
Includes bibliographical references and index.
Keywords: Obama, Barack -- Military leadership; National security -- United States -- Decision making; Afghan War, 2001- -- United States; War on Terrorism, 2001-2009.; United States -- Military policy -- Decision making; Pakistan -- Military relations -- United States; United States -- Officials and employees -- Interviews